2012
DOI: 10.1016/j.biomaterials.2012.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Hollow silica and silica-boron nano/microparticles for contrast-enhanced ultrasound to detect small tumors

Abstract: Diagnosing tumors at an early stage when they are easily curable and may not require systemic chemotherapy remains a challenge to clinicians. In order to improve early cancer detection, gas filled hollow boron-doped silica particles have been developed, which can be used for ultrasound-guided breast conservation therapy. The particles are synthesized using a polystyrene template and subsequently calcinated to create hollow, rigid nanoporous microspheres. The microshells are filled with perfluoropentane vapor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 22 publications
0
97
0
Order By: Relevance
“…Silica nanoparticles have been developed that can enhance image contrast with existing ultrasound technologies by incorporating perfluorocarbons within the particles; however, solid and hollow silica particles have also been shown to be detectable even by non-contrast imaging modalities [6167]. Lui et al showed that systemically administering commercial 100 nm solid silica nanoparticles into mice could generate a detectable ultrasound response [68].…”
Section: Biomedical Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Silica nanoparticles have been developed that can enhance image contrast with existing ultrasound technologies by incorporating perfluorocarbons within the particles; however, solid and hollow silica particles have also been shown to be detectable even by non-contrast imaging modalities [6167]. Lui et al showed that systemically administering commercial 100 nm solid silica nanoparticles into mice could generate a detectable ultrasound response [68].…”
Section: Biomedical Imagingmentioning
confidence: 99%
“…It has been shown that by filling hollow silica nanoparticles with perfluoropentane gas, silica nanoparticles can exhibit substantial contrast under ultrasound imaging [61–63]. The use of hollow silica particles has been explored for tumor detection and imaging with ultrasound.…”
Section: Biomedical Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Silica and iron(III) doped nanoshells have shown promise for in vitro and in vivo ultrasound imaging agents. 76, 80-83 A self-targeting property would potentially broaden their use to drug delivery and tumor localization.…”
Section: Discussionmentioning
confidence: 99%
“…Nanomaterials can damage cell membranes and DNA and lead to cell death through reactive oxygen species (ROS) production; thus, they can destroy cancer cells (1,3). Mesoporous silica nanoparticles (MSN) known as inorganic nanoparticles (4) are non-metal (5), solid, and highly porous oxides (6). These nanoparticles are used broadly in engineering, industry, biomedical applications, cosmetics, and FDA-approved food additives (7).…”
Section: Introductionmentioning
confidence: 99%